Altering internal surface of putty impression material for better recording of tooth preparation margins - Ramin Mosharraf (Mashhad University of Medical Sciences, 2018)
This article describes the clinical procedures for a modified putty-wash impression technique. In this method, the hydraulic pressure induced from planned flowing the wash material from the inner surface of putty impression toward the vestibules pull over the gingival tissues covering the finishing line. This simple method reduces the need to using retraction cord in normal depth finishing line in the gingival sulcus.